A Comprehensive Review on Hyphenated Techniques in Pharmaceutical Analysis - G. Dharmamoorthy (Asian Journal of Pharmaceutics (AJP), 2025)
Hyphenated techniques in pharmaceutical analysis represent a significant advancement in analytical chemistry, combining two or more separation methods with a detection technique to enhance the resolution, sensitivity, and efficiency of analytical processes. This review article discusses various hyphenated techniques employed in pharmaceutical analysis, their principles, applications, advantages, and limitations. Key methods such as high-performance liquid chromatography-mass spectrometry, gas chromatography-mass spectrometry, liquid chromatography with nuclear magnetic resonance spectroscopy, and others are examined in detail, showcasing their role in the development, quality control, and regulatory compliance of pharmaceuticals.